Hubungan Rival Attractiveness dengan Komitmen pada Dewasa Awal Berpacaran di Kota Banjarbaru - Tirani, Iga; Akbar, Sukma Noor; Mayangsari, Marina Dwi (Jurnal Kognisia, 2022)
In early adulthood, commitment is an important aspect of having an intimate relationship such as dating. Commitment in a relationship is defined as an individual's intention to continue the relationship that is being lived. One that affects the level of commitment is rival attractiveness.Someone who feels having a rival in their relationship will tending more to improve commitment in their relationship. This study aimed to understand whether there is correlation of rival attractiveness with commitment of young adults who dating in Banjarbaru city. Hypothesis of this study is there is a correlation of of rival attractiveness with commitment of young adults who dating in Banjarbaru city. Sampel used in this study is 39 persons who currently in dating relationship and within the range of age 21-32 years old which picked using accidental sampling technique. Results found there is a negative correlation between rival attractiveness and dating commitment. Therefore can be concluded that more higher rival attractiveness, then more lower individual dating commitment and vice versa. Aside of rival attractiveness, other factors which influence commitment including attachment styles, personality types, relational satisfaction and relational uncertainty.